Surface properties of radio frequency plasma treated wool and denim fabrics. (5th June 2017) - Hala, Ahmed; Karaca, Gozde Yurdabak; Eren, Esin; Oksuz, Lutfi; Bozduman, Ferhat; Kiristi, Melek; Komur, Ali Ihsan; Gulec, Ali; Oksuz, Aysegul Uygun
Abstract : Purpose: The purpose of this paper was to investigate the effects of hydrochloric acid (HCl), hydrazine, methyl methacrylate, styrene and hexamethyldisiloxane by radio-frequency (rf) plasma graftings on surface properties of wool and denim fabrics. Design/methodology/approach: During plasma treatments, processing time was varied under optimized plasma conditions (50 W, rf: 13.56 MHz). All fabrics were comprehensively investigated by means of scanning electron microscopy-energy dispersive X-ray spectroscopy and contact angle measurements. Findings: The experimental data shows that the rf-plasma processing has important effect on the wettability properties of wool and denim fabrics. The results indicated that HCl plasma treatment significantly improves the hydrophilicity of wool and denim fabrics. Originality/value: The research on wool and denim fabric treatment by plasma is original.